Tamsulosin plus Tadalafil compared with Tamsulosin alone for benign prostate hyperplasia in patients with or without erectile dysfunction: a meta-analysis and meta-regression of randomized controlled trials - Tallal Mushtaq Hashmi (22330558) (2025)
Background Combination pharmacotherapy with tamsulosin plus tadalafil could be a superior strategy compared to conventional monotherapy with tamsulosin in patients with Benign prostatic obstruction (BPO) with or without erectile dysfunction. Methodology A comprehensive search was conducted across PubMed, the Cochrane Library, and Embase to identify studies assessing the efficacy and safety of combination therapy compared with monotherapy in patients with BPO with or without erectile dysfunction. A random effects meta-analysis was performed with R version 4.4.1 using the 'meta' package. Results We included eleven RCTs, with a combined total of 940 patients. Our analysis demonstrated that the combination therapy is associated with a greater reduction in overall IPSS (MD = − 2.78, 95% CI − 3.97 to − 1.59; P < 0.01), IIEF (MD = 2.98, 95% CI 1.64 to 4.33; P < 0.01), QoL score (MD = − 0.58, 95% CI − 0.86 to − 0.30; P < 0.01), PVR (MD = − 9.34, 95% CI = -15.52 to − 3.16; P < 0.01) and a significant improvement in Qmax (MD = 1.04, 95% CI 0.43 to 1.64; P < 0.01) as compared to tamsulosin alone. However, combination therapy resulted in a higher incidence of pain (OR = 5.66, 95% CI 2.56 to 12.52; P < 0.01) and other adverse events (OR = 2.97, 95% CI 1.60 to 5.49; P < 0.01). Conclusion Combination therapy with tamsulosin and tadalafil demonstrated superior efficacy over tamsulosin monotherapy in reducing LUTS, improving quality of life, and enhancing erectile function. However, it was associated with a higher incidence of adverse effects. Other Information Published in: World Journal of Urology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00345-025-05662-w